Fate of Some New Fungicides (Cyprodinil, Fludioxonil, Pyrimethanil, and Tebuconazole) from Vine to Wine - Cabras, Paolo; Angioni, Alberto; Garau, Vincenzo L.; Melis, Marinella; Pirisi, Filippo M.; Minelli, Elizabeth V. [UNESP]; Cabitza, Franco; Cubeddu, Mario (American Chemical Society (ACS), 1997)
The fate of four new fungicides (cyprodinil, fludioxonil, pyrimethanil, and tebuconazole) from the treatment on vine to the production of wine was studied. The influence of clarifying agents (bentonite, charcoal, potassium caseinate, gelatin, and polyvinylpolypyrrolidone) on residue concentrations in wine was also studied. The fungicide residues on grapes showed different decay rates after treatment, with first-order kinetics and half-lives ranging from 8 to 57 days. Grape processing into wine caused considerable residue reduction with cyprodinil (ca. 80%), fludioxonil (ca. 70%), and tebuconazole (ca. 50%) and no reduction with pyrimethanil. The two wine-making techniques employed (with and without maceration) had the same influence on the residue concentrations in wine, except for fludioxonil which showed maximum residue reduction with vinification with maceration. Among the clarifying agents tested, only charcoal showed effective action on the elimination of residue content in wine, proving complete elimination, or almost, of fungicide residues.
Keywords: Fungicides; Residues; Wine-making; Vitaceae; Vitis sp.